Videodiagnosis of External Urinary Meatus Obstruction and Persistent Urachus in Heifer - Borges, Luisa Pucci Buenos; Casas, Vitor Foroni; Pereira, Lucas de Freitas; Crivellenti, Leandro Zuccolotto; Magalhães, Larissa Fernandes; Ayer, Ilan Munhoz; Teixeira, Pedro Paulo Maia (Acta Scientiae Veterinariae, 2017)
Background: Persistent urachus conditions in calves are related to umbilical pathologies and might lead to uroperitoneum abnormalities, especially persistent urachus itself and bladder rupture. Videosurgery could be an interesting option for diagnoses of the genitourinary tract, given the relevance of genitourinary affections in calves. The aim of this report is to describe videosurgery resolution and performance in a case of external urinary meatus obstruction and persistent urachus in a heifer. Case: An eight-month-old Girolando heifer was admitted in the UNIFRAN Veterinary Hospital with the suspicion of persistent urachus. The owner reported that the animal was not urinating, and after a few days, it was noticed the presence of urine leaking from the umbilical site. It was also informed that another veterinarian had previously performed pure iodine infusion in probable urachus area for 5 days in a row in an attempt to obliterate the canal. Significant higher levels of urea, creatinine and fibrinogen were noticed in the exams executed, also leukocytosis and signs of pain when performed abdominal palpation. When urethral sounding was implemented, it showed difficulties and resistance in the introduction of the sound. In the vaginourethrocystoscopy, it was noticed a thin membrane in the external urinary meatus causing complete obstruction, which was easily perforated by the cystoscope sheath, allowing the attainment of urethra and part of cranial bladder inspection. In order to evaluate the flow of the urine, it was applied methylene blue by the cystoscope working channel in the interior of the urethra and the bladder, which was collected by sounding the urachus, confirming presence of persistent urachus. When realized a contrasted x-ray of the bladder, it was noticed extravasation of the contrast into the peritoneum, indicating that a surgical approach should be performed; however the owner did not authorize the realization of any surgical intervention. Antibiotic therapy with cefitiofur (1 mg/kg) and anti-inflammatory therapy with flunixim meglumine (1.1 mg/kg) were initiated, however the patient died after 24 h of therapy. Persistent urachus was confirmed at necropsy, showing malodorous brownish secretion in the umbilicus area. Also, it was observed 2 L of turbid purulent liquid in abdominal cavity, which was filled with fibrin; petechiae in the intestinal serosa; focus of necrosis and bladder rupture concluding that the cause of death was given by rupture of the urinary bladder followed by peritonitis. Discussion: The diagnosis through vaginourethrocystoscopy was important to verify the urethral obstruction. However it was not able to visualize the necrosis area in cranial portion of the bladder due to the size of cystoscope, which was too short and rigid. Video diagnosis was an efficient method for urethral abnormalities and, if necessary a complete bladder evaluation, flexible cystoscope should be used. Urethrocystography is a good option for diagnosis of uroabdomen in heifer and should be performed as a supplementary technique of video diagnosis when injury or rupture of cranial bladder is suspected. Caustic products such as iodinated compounds must not be used if urethra is obstructed, because it can cause extensive necrosis in cranial bladder, uroperitoneum and sepsis, which may lead the patient to death.